2013
DOI: 10.1177/1359104513476719
|View full text |Cite
|
Sign up to set email alerts
|

Finding a voice through ‘The Tree of Life’: A strength-based approach to mental health for refugee children and families in schools

Abstract: The Child and Family Refugee Service at the Tavistock Centre in London has run a series of 'Tree of Life' groups for both parents and children in schools. The groups were developed in response to a concern about the majority of psychological treatments, which focus predominantly on vulnerability factors in refugee populations, and the effect that this can have on those they are attempting to help. In addition, these are modelled on western assumptions, which do not adequately take account of culture. The Tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 9 publications
(6 reference statements)
3
75
0
Order By: Relevance
“…The barriers that exist in accessing services include linguistic difficulties and a lack of understanding about mental health services -what they do, how they might be affected, what their families will consent to, whether they might be admitted to hospital. Few will have knowledge of local services and how to access them or know which problems might best be addressed by such services (Dura-Vila et al, 2013;Hughes, 2014). Mental health services can seem particularly remote as similar services often do not exist in their countries of origin or exist in a very different service model -for example one that emphasizes treatment in large hospitals with little community care or mainly confined to traditional healers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The barriers that exist in accessing services include linguistic difficulties and a lack of understanding about mental health services -what they do, how they might be affected, what their families will consent to, whether they might be admitted to hospital. Few will have knowledge of local services and how to access them or know which problems might best be addressed by such services (Dura-Vila et al, 2013;Hughes, 2014). Mental health services can seem particularly remote as similar services often do not exist in their countries of origin or exist in a very different service model -for example one that emphasizes treatment in large hospitals with little community care or mainly confined to traditional healers.…”
Section: Introductionmentioning
confidence: 98%
“…Access to mental health services can be particularly difficult for those from more vulnerable and deprived contexts (Hughes, 2014;Scheppers et al, 2006). The barriers that exist in accessing services include linguistic difficulties and a lack of understanding about mental health services -what they do, how they might be affected, what their families will consent to, whether they might be admitted to hospital.…”
Section: Introductionmentioning
confidence: 98%
“…Visualities are found to encourage verbalization, but also support the participants when words are not enough (e.g., Katz and Liat 2013;Keats 2009;Lev-Wiesel and Revital 2007;Pain 2012;Weber 2008). As several authors (e.g., German 2013; Gunnarson et al 2006;Gunnarson et al 2010;Hughes 2014) reported advantages when utilizing the shape of a tree with research interview, a life tree was designed for the purposes of the study.…”
Section: Data Collectionmentioning
confidence: 97%
“…Because this process does not require verbalization of traumatic memories, children who are not ready to discuss their history can still benefit from the process. As a result, this approach has been used with children who have experienced trauma and loss in a myriad of settings (Denborough, 2008;Hughes, 2013; The TOL activity is a valuable tool for refugee adolescents to identify their strengths and existent coping skills. In this activity, facilitators first invite a discussion about what members know about trees and their parts (i.e., roots, trunk, branches, leaves, fruit, and seeds).…”
Section: Tree Of Life Activitymentioning
confidence: 99%
“…Davis (2010) discussed how artwork facilitates the organization of thinking and the expression of emotions for those who find it difficult to express themselves in English. Similarly, Hughes (2013) noted that language barriers make it "more difficult to develop trusting therapeutic relationships. Even where interpreters are used, this requires additional skills on the part of practitioners to make this effective" (p. 141).…”
Section: Tree Of Life Activitymentioning
confidence: 99%